"Be a Scientist" Learning media using adobe flash CS3 program containing the materials of the influence of islamic religion and culture in Indonesia for Grade X of vocational school - Ajat Sudrajat; Lantip Diat Prasojo; Zulkarnain Zulkarnain (Journal of Social Studies (JSS), 2018)
This research aims at investigating the needs for image media of "be a scientist" developed using Adobe Flash CS3 program containing the materials of the influence of religion and Islamic culture in Indonesia for learning History of grade X Vocational School and examining the feasibility of "be a Scientist" media developed using Adobe Flash CS3 program containing the materials of the influence of religion and Islamic culture in Indonesia which was developed to be used in the process of learning the history for grade X of Vocational school. This research employed Research and Development (R D) method. The product developed is in the form of "be a scientist" image media using Adobe Flash CS3 program that is appropriate for a learning resource in History subjects. The stages of research include: (1) the preliminary stage, (2) the planning stage of the model as the development of the initial product form, (3) the testing, evaluation and revision stages, and (4) the implementation stage or effectiveness test. Data were colected using FGD (Focus Group Discussion), questionnaires, interviews, observations, and documentation techniques. The validity of the instrument is achieved through expert judgement, while the validity of qualitative data is carried out using source triangulation techniques, theories and methods. Quantitative data analysis was performed using descriptive analysis techniques and qualitative data was carried out using an interactive models. The results show that: Adobe Flash CS 3 media images were needed in vocational schools for the development of history learning. The results of the assessment performed by the experts on material and media indicate that  "be a scientist" image media using Adobe Flash CS3 program for history learning in Vocational High Schools has a good level of feasibility. This shows that the  "be a Scientist" media using the Adobe Flash CS3 program contaiing the material of religious influence and Islamic culture in Indonesia is suitable for history learning in Vocational High Schools grade X.